EphrinB2 in excitatory neurons and astrocytes in the basolateral amygdala controls long-term fear memory formation - Karishma Agarwal; Amira Farhat; Raphael Lamprecht (Communications Biology, 2024)
Abstract EphrinB2 regulates synaptic transmission and morphology however its role in memory formation is unknown. Here we show that deleting ephrinB2 from excitatory neurons in the basolateral amygdala (BLA) of male mice impairs long-term (LTM), but not short-term (STM), fear memory formation. Deleting ephrinB2 from astrocytes in the BLA impairs fear LTM but not STM. Removing ephrinB2 from astrocytes in the BLA reduces the level of the excitatory amino acid transporter 1 (EAAT1) in these cells. Inhibiting EAAT1 activity in the BLA during fear conditioning, by its specific inhibitor UCPH-101, impairs fear LTM showing that EAAT1 in the BLA is needed for fear LTM formation. The administration of ephrinB2 into the BLA during fear conditioning training enhances fear LTM. Moreover, ephrinB2 increases the ability of fear conditioning to activate cells in the BLA as detected by c-Fos labeling. EphrinB2 therefore determines the threshold for fear memory formation. In contrast to mature neurons, we show that ephrinB2 in neural stem cells (NSCs) is not needed for fear LTM. Our study shows that ephrinB2 in the BLA determines the strength of long-term memory consolidation.